PENGARUH TOTAL QUALITY MANAGEMENT (TQM), SISTEM PENGUKURAN KINERJA DAN SISTEM PENGHARGAAN (REWARD) TERHADAP KINERJA MANAJERIAL CV. SINGKONG ARTO MAS KEPANJEN-MALANG - Muksyfatul Maulidiyah; Hadi Sunaryo; Afi Rachmat Slamet (UNIVERSITAS ISLAM MALANG, 2017)
AbstractThis study aims to determine the effect of total quality management(TQM), performance measurement system and reward system on managerialperformance. Population of this research is all employee CV. Singkong Arto Maswhich amounted to 215 employees. The sample in this research using purposivesampling technique as many as 55 respondents. Data analysis method used in thisresearch is multiple linear regression.The results of this study partially total quality management (TQM) havea significant negative effect on managerial performance, while performancemeasurement system and reward system have no effect on managerialperformance. Simultaneously total quality management (TQM), performancemeasurement system and reward system have an effect on managerialperformance.Keywords : Total Quality Management (TQM), performance measurement system,reward system, managerial performance.